Biological response to geochemical and hydrological processes in a shallow submarine cave - RADOLOVIĆ, M.; BAKRAN-PETRICIOLI, T.; PETRICIOLI, D.; SURIĆ, M.; PERICA, D. (Mediterranean Marine Science, 2015)
The Croatian coastal karst abounds in submerged caves that host a variety of environmental conditions depending on the geomorphology, depth and submarine groundwater discharge. One example is the Y-Cave, a shallow, mostly submerged, horizontal cave on Dugi Otok Island, on the eastern Adriatic coast. This study was aimed at examining the temporal and spatial variability of the marine cave environment, including temperature, salinity, light intensity, cave morphology and hydrodynamism, along with the dissolutional effect caused by the mixing of sea and freshwater. The general distribution of organisms in the Y-Cave was positively correlated to the light gradient and reduced water circulation, thus the highest species diversity and abundance were recorded in the front part of the cave. The phylum Porifera was the most dominant group, and the poriferan species diversity in the cave ranks among the ten highest in the Mediterranean. The middle part of the cave, although completely dark, hosts an abundant population of the gastropod Homalopoma sanguineum and clusters of the gregarious brachiopod Novocrania anomala, whose presence could be connected to tidal hydrodynamics. The absence/scarcity of sessile marine organisms and pronounced corrosion marks at shallow depths inside the cave suggest a freshwater impact in the upper layers of the water column. A year long experiment with carbonate tablets revealed three different, independent ongoing processes affected by the position in the cave: bioaccumulation, dissolution and mechanical erosion. The results of long-term temperature readings also revealed water column stratification within the cave, which was not disturbed by either tidal or wave action. The shallow, partly submerged and relatively small Y-Cave is characterised by a suite of complex environmental conditions, which, together with the resulting distribution of organisms, are unique to this cave.